Personal Values in Village Fund Fraud Prevention - Audry Leiwakabessy; Monika Handojono; Angel Merlyn Pattimahu (Univiversitas Dr. Djar Wattiheluw, 2024)
The increase of the village fund over the years, on the one hand - creates many opportunities for the village governments to improve their quality of life. However, on the other hand, it could lead to misuse and, to some extent, it is committed to fraud in the management process. Fraud is an unlawful act that causes many losses and benefits the perpetrator. Fraud may occur in both the private and public sectors (government). This research aims to empirically test the influence of Idealism and Morality on Fraud Prevention in Village Fund Financial Management. By using the Simple Random Sampling technique, the study is participated by Village Government Administrators and Village Consultative Councils in Teluk Ambon District as the population with the samples consisted of Village Government Administrators and Village Consultative Bodies from 6 (six) Villages in the Teluk Ambon District area. The research found that morality (p=0.008) and idealism (p=0.000) positively prevent fraud in village fund management. The result confirmed that when people have knowledge, understanding, and idealism, as well as personal values such as morals and ethics, they tend to avoid fraud. The research recommends conducting an experiment that focuses on groups to collect data to reduce internal validity problems. It may also examine other variables that can explain a more significant influence on fraud prevention.